Sodium modified mesoporous aluminum as well as preparation method and application thereof

By dispersing sodium metal in the mesoporous aluminum substrate, the sodium-modified mesoporous aluminum catalyst was prepared, which solved the problem of inefficiency and rapid inactivation of alumina catalysts when treating carbon tetrafluoride, and achieved efficient and long-life catalysis Effect.

CN119500094AActive Publication Date: 2025-02-25CENT SOUTH UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411417289.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-02-25
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

In the prior art, alumina catalysts have problems of low treatment efficiency and rapid catalyst deactivation when treating carbon tetrafluoride.

Method used

Sodium modified mesoporous aluminum is used as a catalyst to uniformly disperse sodium metal in the mesoporous aluminum substrate to improve the surface oxygen content and acidic site content of the catalyst, thereby improving the decomposition efficiency of carbon tetrafluoride.

Benefits of technology

It significantly improves the decomposition efficiency of carbon tetrafluoride, extends the life of the catalyst, and avoids the problem of catalyst poisoning caused by carbon accumulation in common technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500094A_ABST
    Figure CN119500094A_ABST
Patent Text Reader

Abstract

The invention provides sodium modified mesoporous aluminum and a preparation method and application thereof.The sodium modified mesoporous aluminum comprises a mesoporous aluminum substrate and metal sodium, the metal sodium is evenly dispersed in the mesoporous aluminum substrate, and the mesoporous aluminum substrate is porous nanoparticles in an amorphous state; the mass ratio of the oxygen element on the surface of the sodium modified mesoporous aluminum is 44.88%, the specific surface area of the mesoporous aluminum substrate is larger than or equal to 100 m < 2 > / g, and the aperture of the mesoporous aluminum substrate is 2-50 nm. The sodium-modified mesoporous aluminum provided by the invention can keep a high catalytic rate within a long time, and is long in service life, remarkable in effect and worthy of popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the application field of a catalyst for decomposing carbon tetrachloride, and in particular to sodium-modified mesoporous aluminum and a preparation method and application thereof. Background Art

[0002] Carbon tetrafluoride is a strong greenhouse gas with a global warming potential (GWP) thousands of times that of carbon dioxide, and its lifespan in the atmosphere is extremely long, up to tens of thousands of years. Therefore, the degradation of carbon tetrafluoride is of great significance for slowing global warming and reducing the greenhouse effect.

[0003] However, carbon tetrafluoride has low reactivity and high stability, and it is difficult to degrade carbon tetrafluoride into harmless or low-harm substances. Since the electronegativity of the fluorine atom (F) in the carbon tetrafluoride molecule is large and the carbon-fluorine bond (CF bond) has a high bond energy, this high bond energy makes the CF bond extremely difficult to break at room temperature and pressure, so carbon tetrafluoride is not easy to react chemically. In addition, the carbon tetrafluoride molecule has a regular tetrahedral spatial structure, and the four fluorine atoms are symmetrically distributed around the carbon atom. This symmetrical structure makes the carbon tetrafluoride molecule highly stable in both physical and chemical properties.

[0004] The existing technology has a carbon tetrafluoride degradation technology that uses alumina as a catalyst coupled with plasma technology. Although activated alumina is a highly efficient fluoride adsorbent, it still has the disadvantage of low treatment efficiency when treating carbon tetrafluoride - limited by the adsorption capacity, once the alumina reaches a saturated state, the decomposition efficiency will drop significantly, thereby affecting the treatment effect of carbon tetrafluoride. In addition, the surface hydroxyl group of activated alumina is unstable. When O2 exists in the flue gas, the surface hydroxyl group is easily destroyed under the action of plasma, causing the activated alumina to quickly deactivate.

[0005] Based on the above, it is urgent to study a sodium-modified mesoporous aluminum and its preparation method and application, in order to solve the above problems. Summary of the invention

[0006] The main purpose of the present invention is to provide a sodium-modified mesoporous aluminum and a preparation method and application thereof, aiming to solve the technical problem of low efficiency in degrading carbon tetrafluoride after catalyst saturation in the common technology.

[0007] To achieve the above object, the present invention provides a sodium-modified mesoporous aluminum, comprising a mesoporous aluminum substrate and metallic sodium, wherein the metallic sodium is uniformly dispersed in the mesoporous aluminum substrate, and the mesoporous aluminum substrate is porous nanoparticles in an amorphous state;

[0008] The mass proportion of oxygen elements on the surface of the sodium-modified mesoporous aluminum is 40% to 50%, the mass proportion of sodium elements on the surface of the sodium-modified mesoporous aluminum is 1% to 20%, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50 nm.

[0009] Furthermore, the mass proportion of the sodium element on the surface of the sodium-modified mesoporous aluminum is 3-5%.

[0010] The present invention provides a method for preparing the sodium-modified mesoporous aluminum as described in any one of the above, comprising the steps of:

[0011] Mixing polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture;

[0012] The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain sodium-modified mesoporous aluminum;

[0013] The metal nitrate includes sodium nitrate, and the added amount ratio of the polyether, the nitric acid, the aluminum isopropoxide and the sodium nitrate is 1g:1.5ml:10mmol:0.01-0.05g, wherein the concentration of the nitric acid is 65%.

[0014] Furthermore, the calcination temperature is 500-1000° C., and the calcination time is 1-8 hours.

[0015] Furthermore, in the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture, the polyether is dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

[0016] Furthermore, the temperature of the drying treatment is 50 to 80° C., and the duration of the drying treatment is 6 to 12 hours.

[0017] Furthermore, the temperature of the calcination treatment includes 600°C, and the calcination treatment includes: heating the solid particles obtained by the drying treatment to 600°C at a heating rate of 1-10°C / min, and calcining for 3-6h to obtain the sodium-modified mesoporous aluminum.

[0018] The present invention also provides a use of sodium-modified mesoporous aluminum prepared by any one of the preparation methods described above in carbon tetrafluoride treatment, comprising the steps of:

[0019] The carbon tetrafluoride-containing flue gas to be treated flows through the sodium-modified mesoporous aluminum in a plasma field for decomposition treatment, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10-50 mL / min, and the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas is 1%-20%;

[0020] The sodium-modified mesoporous aluminum is placed in the discharge region of the plasma field.

[0021] Furthermore, the input voltage of the plasma reactor forming the low-temperature plasma field is 20-40 kV.

[0022] Furthermore, the oxygen concentration in the carbon tetrafluoride-containing flue gas is 5%-20%.

[0023] The beneficial effects achieved by the present invention are:

[0024] The sodium-modified mesoporous aluminum provided by the present invention has high efficiency in decomposing carbon tetrafluoride. The surface of the sodium-modified mesoporous aluminum is rich in hydroxyl groups, so it has excellent performance when applied to the degradation of CF4. With the doping of sodium elements, the presence of Na is conducive to the activation of adsorbed water, promotes the formation of surface hydroxyl groups, increases the content of acidic and basic sites of mesoporous aluminum, and further promotes the decomposition of CF4. At the same time, after sodium doping, the surface oxygen content of the mesoporous aluminum base is significantly improved, which significantly enhances the decomposition effect of carbon tetrafluoride, breaking through the decomposition efficiency peak of alumina used in the degradation of carbon tetrafluoride in the commonly used technology (that is, under specific conditions, the highest efficiency point reached by the degradation or decomposition of carbon tetrafluoride, indicating the proportion of carbon tetrafluoride removed or converted within a certain period of time).

[0025] The sodium-modified mesoporous aluminum provided by the present invention has high catalytic activity and long life. The surface oxygen element of the sodium-modified mesoporous aluminum is 44.88%, and the sodium element accounts for 3.25%. Based on the increase of the surface oxygen element after sodium doping, Na doping promotes the combination of C and O in CF4 to generate gas escape, significantly reducing C deposition, and synergizing the increase of the total acid content and strong acid content in the mesoporous aluminum after sodium doping, effectively alleviating the catalyst poisoning problem caused by C and F deposition in the catalytic reaction process in the common technology, and improving the catalytic activity of the sodium-modified mesoporous aluminum, so that it can maintain a high catalytic rate for a long time.

[0026] The morphology of the mesoporous aluminum substrate in the sodium-modified mesoporous aluminum of the present invention is optimized. With the doping of sodium element, sodium is evenly dispersed in the mesoporous aluminum substrate, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, the pore size of the mesoporous aluminum substrate is 2 to 50nm, and the morphology of the mesoporous aluminum substrate is transformed into dispersed porous nanoparticles. With the morphology optimization caused by the modification of the mesoporous aluminum substrate, sufficient active sites are provided for the adsorption and catalysis of carbon tetrafluoride, thereby improving the activity of the catalyst. In addition, with the increase of the specific surface area of ​​the mesoporous aluminum substrate, the dispersion of carbon tetrafluoride particles will also increase, which helps carbon tetrafluoride to be evenly distributed on the catalyst surface, reduce mass transfer resistance, and further improve degradation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0028] Figure 1 This is a morphology detection diagram of each metal-doped mesoporous aluminum catalyst using SEM-EDS in Analysis Example 1 of the present invention, wherein: Figure 1 (a) is the SEM image of mesoporous aluminum. Figure 1 (b) is the SEM image of Na / mesoporous aluminum. Figure 1 (c) is the SEM image of Ce / mesoporous aluminum. Figure 1 (d) is the EDS image of mesoporous aluminum. Figure 1 (e) is the EDS image of Na / mesoporous aluminum. Figure 1 (f) is the EDS image of Ce / mesoporous aluminum;

[0029] Figure 2 This is the XRD analysis diagram of each metal-doped mesoporous aluminum catalyst in Analysis Example 1 of the present invention.

[0030] Figure 3 The microscopic morphology structure diagram of each metal-doped mesoporous aluminum catalyst obtained by TEM in the analysis example 1 of the present invention, wherein Figure 3 (a) is the TEM image of mesoporous aluminum. Figure 3 (b) is the TEM image of Na / mesoporous aluminum. Figure 3 (c) is the TEM image of Ce / mesoporous aluminum.

[0031] Figure 4 (a) is a schematic diagram showing the effect of different synthesis methods on the decomposition efficiency of Na / mesoporous aluminum on CF4 in Analysis Example 2 of the present invention. Figure 4 (b) is a schematic diagram showing the effect of different sodium doping concentrations of Na / mesoporous aluminum on the decomposition efficiency of CF4 in Analysis Example 2 of the present invention.

[0032] Figure 5 (a) is a schematic diagram of the decomposition efficiency of carbon tetrafluoride at a flow rate of 20 mL / min Na / mesoporous aluminum, mesoporous aluminum and plasma alone in the analysis example 3 of the present invention; Figure 5 (b) is a schematic diagram of the decomposition efficiency of carbon tetrafluoride at a flow rate of 50 mL / minNa / mesoporous aluminum, mesoporous aluminum, and plasma alone in the present invention in Example 3.

[0033] Figure 6 (a) Analysis Example 3 of the present invention is a schematic diagram comparing the decomposition efficiency of carbon tetrafluoride by various metal-doped mesoporous aluminum when the flue gas flow rate is 20 mL / min; Figure 6(b) is a schematic diagram comparing the decomposition efficiency of carbon tetrafluoride by various metal-doped mesoporous aluminum when the flue gas flow rate is 50 mL / min in Analysis Example 3 of the present invention.

[0034] Figure 7 Schematic diagram of the effect of the oxygen composition of carbon tetrafluoride on the decomposition efficiency of carbon tetrafluoride in Na / mesoporous aluminum or plasma alone in Analysis Example 4 of the present invention.

[0035] Figure 8 Schematic diagram of the effect of O2 on the decomposition performance of mesoporous aluminum CF4 doped with different metals in the analysis example 4 of the present invention, wherein Figure 8 (a) Comparison of the CF4 degradation efficiency of various metal-doped mesoporous aluminum under oxygen-containing flue gas conditions; Figure 8 (b) Comparison of CF4 degradation efficiency of composite metal-doped mesoporous aluminum under oxygen-containing flue gas conditions.

[0036] Fig. 9 This is the SEM detection image of Na / mesoporous aluminum before and after the reaction under the condition of O2 concentration of 10% in the analysis example 5 of the present invention, wherein Fig. 9 (a) is the morphology of Na / mesoporous aluminum before reaction. Fig. 9 (b) The morphology after Na / mesoporous aluminum reaction.

[0037] Fig.10 This is a graph showing the change in element content before and after the Na / mesoporous aluminum reaction in analysis example 5 of the present invention.

[0038] Fig.11 This is the SEM detection image of Na / mesoporous aluminum before and after the reaction in Analysis Example 5 of the present invention.

[0039] Fig.12 The XRD and TEM images of Na / mesoporous aluminum before and after the reaction under the condition of 10% O2 concentration in the analysis example 6 of the present invention are shown in FIG. Fig.12 (a) is the XRD diffraction pattern of Na / mesoporous aluminum after reaction; Fig.12 (b) TEM image of Na / mesoporous aluminum after reaction.

[0040] Fig.13 This is a graph showing the changes in the surface acid sites of Na / mesoporous aluminum before and after the reaction under the condition of an O2 concentration of 10% in the analysis example 7 of the present invention, wherein: Fig.13 (a) is the NH3-TPD diagram of Na / mesoporous aluminum, Ce / mesoporous aluminum and mesoporous aluminum before reaction. Fig.13 (b) NH3-TPD diagram before Na / mesoporous aluminum reaction.

[0041] Fig.14 This is a graph showing the change in the Na / mesoporous aluminum acidity before and after the reaction under the condition of an O2 concentration of 10% in the analysis example 7 of the present invention, wherein: Fig.14(a) is the infrared spectrum of pyridine adsorption before Na / mesoporous aluminum reaction. Fig.14 (b) is the infrared spectrum of pyridine adsorption after Na / mesoporous aluminum reaction.

[0042] Fig.15 This is the analysis diagram of the Na / mesoporous aluminum alkaline site before and after the reaction in the analysis example 7 of the present invention, wherein Fig.15 (a) is the CO2-TPD diagram of mesoporous aluminum and Na / mesoporous aluminum. Fig.15 (b) CO2-TPD diagram of Na / mesoporous aluminum before and after the reaction.

[0043] Fig.16 This is the XPS graph of Na / mesoporous aluminum before and after the reaction under the condition of 10% O2 concentration in the analysis example 8 of the present invention, wherein: Fig.16 (a) is the 2p orbital electron energy spectrum of Na / mesoporous aluminum element before and after the reaction. Fig.16 (b) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum oxide before and after the reaction. Fig.16 (c) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum sodium element before and after the reaction. Fig.16 (d) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum fluoride element.

[0044] Fig.17 (a) is the NH3-TPD diagram of O2 pretreated and untreated Na / mesoporous aluminum in analytical example 9 of the present invention; Fig.17 (b) CO2-TPD of O2-pretreated and untreated Na / mesoporous aluminum in Analytical Example 9 of the present invention.

[0045] Fig.18 This is the gas chromatogram of the decomposition of CF4 tail gas by metal-doped mesoporous aluminum in Analysis Example 9 of the present invention.

[0046] Fig.19 This is a comparison of the decomposition efficiency of CF4 using mesoporous aluminum in Analysis Example 10 of the present invention and commercial Al2O3 as catalysts.

[0047] Fig. 20 (a) is the NH3-TPD test graph of mesoporous aluminum before and after the reaction in Analysis Example 11 of the present invention; Fig. 20 (b) is the NH3-TPD test diagram of mesoporous aluminum and commercial Al2O3 in the analytical example 11 of the present invention.

[0048] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with the implementation methods and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] It should be noted that, in the absence of conflict, the following embodiments and features in the embodiments can be combined with each other. It should also be understood that the terms used in the embodiments of the present invention are intended to describe specific embodiments rather than to limit the scope of protection of the present invention.

[0051] Unless otherwise defined, all technical and scientific terms used in the present invention are consistent with the prior art mastery of the technicians in this technical field and the records of the present invention. Any methods, equipment and materials of the prior art similar to or equivalent to the methods, equipment and materials in the embodiments of the present invention can also be used to implement the present invention. It should be known by those skilled in the art that, as an explanation of the present application document, without affecting the actual understanding of the technical solution of the present application, "Intensity (au)" can be expressed as intensity, "Stress" can be expressed as stress, "Strain" can be expressed as strain, "Grain size" can be expressed as grain size, and "Frequency" can be expressed as frequency.

[0052] When the embodiments give numerical ranges, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. The test methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The materials or reagents required in the following embodiments are commercially available unless otherwise specified.

[0053] In the commonly used technology, during the continuous use of alumina catalysts, the degradation of carbon tetrafluoride produces carbon deposits or other byproducts. These carbon deposits gradually accumulate on the catalyst surface, covering some active sites, resulting in a reduction in the effective surface area of ​​the catalyst and a gradual decrease in the reaction activity. At the same time, the increase in carbon deposits may also cause the catalyst pores to decrease, further affecting the contact between the reactants and the active sites, thereby reducing the catalytic efficiency, and ultimately leading to a significant decrease in the decomposition efficiency of alumina and the deactivation of the alumina catalyst.

[0054] Specifically, referring to the analysis example 10 of the present invention, the decomposition efficiency of the alumina catalyst drops below 50% at 300 min, which is equivalent to the decomposition efficiency of CF4 by plasma alone, indicating that Al2O3 has been deactivated at this time.

[0055] In order to solve the above problems, the present invention provides a sodium-modified mesoporous aluminum, comprising a mesoporous aluminum substrate and a metal, wherein the metal is uniformly dispersed in the mesoporous aluminum substrate, the mesoporous aluminum substrate is porous nanoparticles in an amorphous state, and the metal comprises sodium;

[0056] The mass proportion of oxygen elements on the surface of the sodium-modified mesoporous aluminum is 40% to 50%.

[0057] Exemplarily, the mass proportion of oxygen elements on the surface of the sodium mesoporous aluminum is 44.88%.

[0058] The sodium-modified mesoporous aluminum provided by the present invention has high efficiency in decomposing carbon tetrafluoride. The surface of the sodium-modified mesoporous aluminum is rich in hydroxyl groups, so it has excellent performance when applied to the degradation of CF4. With the doping of sodium elements, the presence of Na is conducive to the activation of adsorbed water, promotes the formation of surface hydroxyl groups, increases the content of acidic and basic sites of mesoporous aluminum, and further promotes the decomposition of CF4. At the same time, after sodium doping, the surface oxygen content of the mesoporous aluminum base is significantly improved, which significantly enhances the decomposition effect of carbon tetrafluoride, breaking through the decomposition efficiency peak of alumina used in the degradation of carbon tetrafluoride in the commonly used technology (that is, under specific conditions, the highest efficiency point reached by the degradation or decomposition of carbon tetrafluoride, indicating the proportion of carbon tetrafluoride removed or converted within a certain period of time).

[0059] The sodium-modified mesoporous aluminum provided by the present invention has high catalytic activity and long service life. The surface oxygen element of the sodium-modified mesoporous aluminum is 44.88%. Based on the increase of the surface oxygen element after sodium doping, Na doping promotes the combination of C and O in CF4 to generate gas escape, significantly reducing C deposition, and synergistically increasing the total acid content and strong acid content in the mesoporous aluminum after sodium doping, effectively alleviating the catalyst poisoning problem caused by C and F deposition in the catalytic reaction process in the common technology, and improving the catalytic activity of the sodium-modified mesoporous aluminum, so that it can maintain a high catalytic rate for a long time.

[0060] Specifically, referring to the research in Analysis Example 3 of the present invention, the sodium-modified mesoporous aluminum can reach a stable value of about 60% after 500 minutes, overcoming the catalyst poisoning problem caused by C and F deposition.

[0061] In some embodiments, the specific surface area is ≥ 100 m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50 nm.

[0062] like Figure 1As shown in (b), with the doping of sodium, sodium is evenly dispersed in the mesoporous aluminum substrate, and the morphology of the mesoporous aluminum substrate is transformed into dispersed porous nanoparticles. With the morphology optimization caused by the modification of the mesoporous aluminum substrate, sufficient active sites are provided for the adsorption and catalysis of carbon tetrafluoride, thereby improving the activity of the catalyst. In addition, with the increase of the specific surface area of ​​the mesoporous aluminum substrate, the dispersion of carbon tetrafluoride particles will also increase, which helps carbon tetrafluoride to be evenly distributed on the catalyst surface, reduce mass transfer resistance, and further improve degradation efficiency.

[0063] In some embodiments, the metal of the sodium-modified mesoporous aluminum includes sodium, and the sodium element in the sodium-modified mesoporous aluminum (ie, Na / mesoporous aluminum, the same below) modified with sodium may account for 3-5%.

[0064] Exemplarily, the mass fraction of O element on the surface of Na / mesoporous aluminum is 44.88%, and the mass fraction of Na element is 3.25%.

[0065] The present invention provides a method for preparing sodium-modified mesoporous aluminum, comprising the steps of:

[0066] S1. Mix polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture.

[0067] In some embodiments, the metal nitrate includes sodium nitrate, and the ratio of the added amounts of the polyether, the nitric acid, the aluminum isopropoxide and the sodium nitrate is 1 g:1.5 ml:10 mmol:0.01-0.05 g, wherein the concentration of the nitric acid includes 65%.

[0068] In the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain the mixture, the polyether can be dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

[0069] Exemplarily, the solvent may be ethanol.

[0070] Exemplarily, the concentration of nitric acid may be 65%.

[0071] S2. The mixture is stirred, dried and calcined in sequence to obtain sodium-modified mesoporous aluminum.

[0072] Wherein, the temperature of the calcination treatment is 600-800° C., and the duration of the calcination treatment is 1-8 hours.

[0073] Exemplarily, the stirring process may include the steps of: covering the mixture with plastic wrap and stirring at room temperature for about 6 hours.

[0074] The temperature of the drying process may be 50 to 80° C., and the duration of the drying process may be 6 to 12 hours.

[0075] In some embodiments, the calcination temperature includes 600°C, and the calcination includes: heating the solid particles obtained by the drying process to 600°C at a heating rate of 2°C / min, and calcining for 3 to 6 hours to obtain the sodium-modified mesoporous aluminum.

[0076] The present invention also provides the use of sodium-modified mesoporous aluminum prepared by the above preparation method in carbon tetrafluoride treatment, comprising the steps of:

[0077] The flue gas containing carbon tetrafluoride to be treated flows through the sodium-modified mesoporous aluminum in a plasma field for decomposition treatment.

[0078] In some embodiments, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field may be 10-50 mL / min, the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas may be 1%-20%, and the concentration of oxygen in the carbon tetrafluoride-containing flue gas may be 5%-20%.

[0079] For example, the concentration of oxygen in the flue gas containing carbon tetrafluoride may be 10%.

[0080] Referring to the research in Analysis Example 4 of the present invention, it can be seen that an appropriate concentration of O2 can improve the decomposition efficiency and reaction stability of CF4 by sodium-modified mesoporous aluminum.

[0081] It can also be referred to the research in Analysis Example 8 of the present invention. It can be seen that after Na doping, Al-OH is transformed into a double-bridged hydroxyl group (HO-μbri(Na-Al)) between Na and Al, which increases the stability of -OH in Na / mesoporous aluminum, making it less likely to be destroyed by O2, and further improving the decomposition efficiency and reaction stability of CF4 by sodium-modified mesoporous aluminum under O2 conditions.

[0082] In comparison, in common technologies, due to the electronegativity of O2, when the concentration of O2 in the reaction system reaches a certain level, it will compete with CF4, reducing the energy of plasma acting on CF4, resulting in a decrease in the efficiency of plasma decomposition of CF4. In addition, the O2 introduced under the action of plasma will react with mesoporous aluminum, changing the active sites on the surface of mesoporous aluminum, resulting in a decrease in the efficiency of mesoporous aluminum decomposition of CF4.

[0083] The mesoporous aluminum may be disposed in a discharge region of the plasma field.

[0084] In some embodiments, the input voltage of the plasma reactor for forming the plasma field may be 20-40 kV.

[0085] For further understanding of the present invention, examples are given below:

[0086] Example 1

[0087] Preparation of sodium-modified mesoporous aluminum by doping method

[0088] 1g of polyether P123 was dissolved in 20mL of ethanol at room temperature, and 1.5mL of 65% nitric acid, 2.04g (10mmol) of aluminum isopropoxide, and 0.025g of sodium nitrate were added under vigorous stirring. Cover the mixture with plastic wrap, stir at room temperature for about 6h, and heat it in a drying oven at 60°C for two days to evaporate the solution. Finally, the obtained solid particles were calcined at 600°C at a heating rate of 2°C / min for 5h to obtain a sodium-modified mesoporous aluminum product, Na / mesoporous aluminum, wherein the sodium doping concentration of Na / mesoporous aluminum was 3-5%, that is, the mass fraction of sodium element in the surface elements of Na / mesoporous aluminum accounted for 3-5%.

[0089] The above steps remain unchanged, only 0.025g of sodium nitrate is replaced with 0.434g of cerium nitrate to obtain cerium-modified mesoporous aluminum - Ce / mesoporous aluminum.

[0090] Comparative Example 1

[0091] The other steps in Example 1 remain unchanged, and only 0.025 g of sodium nitrate is replaced with 0.12 mL of manganese nitrate to obtain manganese-doped mesoporous aluminum - Mn / mesoporous aluminum.

[0092] Among them, the doping concentration of metal elements in Ce / mesoporous aluminum and Mn / mesoporous aluminum is about 5%.

[0093] Comparative Example 2

[0094] Preparation of sodium-modified mesoporous aluminum by loading method

[0095] Dissolve 1 g of polyether P123 in 20 mL of ethanol at room temperature, add 1.5 mL of 65% nitric acid and 2.04 g (10 mmol) of aluminum isopropoxide while stirring the solution. Cover the mixture with plastic wrap, stir at room temperature for about 6 hours, and then heat it in a drying oven at 60°C for 2 days to evaporate the solution. Finally, calcine the obtained solid particles at 600°C for 5 hours at a heating rate of 2°C / min to obtain mesoporous aluminum.

[0096] Mesoporous aluminum was dispersed in 50 mL of deionized water and ultrasonically treated for 30 min. After the solid was completely dissolved, 0.025 g of NaNO3 was added and ultrasonic treatment was continued for 30 min. The obtained suspension was poured into a rotary evaporator and evaporated at 75 °C for 2 h. Finally, the obtained solid sample was calcined at 600 °C for 5 h at a heating rate of 2 °C / min to obtain Na-loaded mesoporous aluminum.

[0097] Comparative Example 3

[0098] The other steps in Example 1 remain unchanged, and only the amount of sodium nitrate added is changed to obtain Na / mesoporous aluminum with sodium doping amounts of 2%, 10% and 20%, respectively.

[0099] Analysis example 1

[0100] The morphology of metal-doped mesoporous aluminum catalysts was determined by SEM-EDS. Figure 1 As shown, Figure 1 (a) is the SEM image of mesoporous aluminum. Figure 1 (b) is the SEM image of Na / mesoporous aluminum. Figure 1 (c) is the SEM image of Ce / mesoporous aluminum. Figure 1 (d) is the EDS image of mesoporous aluminum. Figure 1 (e) is the EDS image of Na / mesoporous aluminum. Figure 1 (f) is the EDS image of Ce / mesoporous aluminum.

[0101] It can be seen that there are a large number of pore structures on the surface of mesoporous aluminum. After the introduction of Na or Ce, its morphology changes to dispersed nanoparticles, indicating that metal doping will change the morphology of mesoporous aluminum. EDS results show that the O element content on the surface of mesoporous aluminum is 26.81%, and the Al element content is 59.85%. After Na doping, the proportion of O elements on the surface of Na / mesoporous aluminum increased to 44.88%, and the proportion of Na elements was 3.25%. After Ce doping, the proportion of O elements on the surface of Ce / mesoporous aluminum was 43.61%, and the proportion of Ce elements was 7.84%.

[0102] The results show that both Na and Ce doping will change the morphology of mesoporous aluminum and significantly increase the surface oxygen content, which is an important factor in enhancing the catalytic decomposition of CF4 by mesoporous aluminum.

[0103] The physical structures of the above catalysts were analyzed by XRD. Figure 2 As shown. There is no obvious characteristic peak in the XRD spectrum of mesoporous aluminum, indicating that the mesoporous aluminum is in an amorphous state. After using Na, Mn, and Ce respectively, there is no characteristic peak belonging to aluminum oxide, and no characteristic peak belonging to Na, Mn, and Ce oxides, indicating that Na, Mn, and Ce do not change the phase structure of mesoporous aluminum, and are evenly dispersed into the mesoporous aluminum substrate.

[0104] The microstructure of the above catalysts was analyzed by TEM. Figure 3 As shown, Figure 3 (a) is the TEM image of mesoporous aluminum. Figure 3 (b) is the TEM image of Na / mesoporous aluminum. Figure 3(c) is the TEM image of Ce / mesoporous aluminum. Mesoporous aluminum presents a typical wormhole-like microstructure with no lattice fringes on the surface, indicating that it has porous and amorphous structural characteristics. After Na doping, mesoporous aluminum still maintains a wormhole-like microstructure and has no obvious diffraction rings, which belongs to an amorphous structure. After Ce doping, the material becomes more compact, but still remains amorphous.

[0105] Analysis example 2

[0106] Study on the influence of different synthesis methods on the decomposition efficiency of carbon tetrafluoride in Example 1 (doping method) and Comparative Example 2 (loading method)

[0107] Flue gas containing carbon tetrafluoride with a CF4 concentration of 10% and a flue gas flow rate of 50 mL / min flows through a plasma field to couple Na / mesoporous aluminum or Na-loaded mesoporous aluminum, wherein the plasma field is formed by a plasma reactor with an input voltage of 25 kV.

[0108] like Figure 4 As shown, Figure 4 (a) is the effect of the synthesis method on the decomposition efficiency of CF4, Figure 4 (b) Effect of doping concentration. The peak decomposition efficiency of Na / mesoporous aluminum prepared by doping method for CF4 is 76%, 6% higher than that of mesoporous aluminum. However, the decomposition efficiency of Na / mesoporous aluminum prepared by loading method is only 62%, 8% lower than that of mesoporous aluminum.

[0109] The loading method first synthesizes mesoporous aluminum and then loads Na on the surface. Therefore, Na is more likely to aggregate on the surface of mesoporous aluminum and block the pores, thereby reducing the CF4 decomposition efficiency of the catalyst. The doping method directly adds Na to the solution for preparing mesoporous aluminum. Na is more dispersed in the catalyst, increasing the contact area between Na and CF4 and improving the decomposition efficiency of CF4.

[0110] The effect of Na doping concentration on CF4 decomposition efficiency was studied. Figure 4 (b) When the Na doping amount is 5%, the Na / mesoporous aluminum decomposition efficiency of CF4 can reach up to 76%, which is 13%, 20%, and 16% higher than when the Na doping amount is 2%, 10%, and 20%, respectively. When the doping concentration is too low, it is not enough to achieve the modification effect, while too high a concentration will cause the particles to agglomerate, thus affecting the catalytic efficiency. Therefore, doping with 5% Na is the best method for preparing Na / mesoporous aluminum catalysts.

[0111] Analysis example 3

[0112] Study on the effect of flue gas flow rate on the decomposition efficiency of carbon tetrafluoride

[0113] Flue gas with a concentration of 10% flows through plasma field coupled Na / mesoporous aluminum, plasma field coupled mesoporous aluminum and a single low-temperature plasma field.

[0114] like Figure 5 As shown, Figure 5 (a) is the decomposition efficiency of CF4 by Na / mesoporous aluminum and mesoporous aluminum at a flow rate of 20 mL / min. Figure 5 (b) Decomposition efficiency of CF4 at a flow rate of 50 mL / min for Na / mesoporous aluminum and mesoporous aluminum.

[0115] When the flue gas flow rate is 20mL / min, the decomposition efficiency of CF4 by mesoporous aluminum reaches a peak value of 82% after 100 minutes of reaction, and the mesoporous aluminum is close to deactivation after 500 minutes. Under the same conditions, the decomposition efficiency of CF4 by Na / mesoporous aluminum reaches a peak value of 86% after 150 minutes, and reaches a stable value of about 60% after 500 minutes. When the flue gas flow rate is increased to 50mL / min, the peak value of the decomposition efficiency of CF4 by mesoporous aluminum can reach 70%, but it will still be deactivated after 500 minutes of reaction. The peak value of the decomposition efficiency of CF4 by Na / mesoporous aluminum is about 76%. After 500 minutes of reaction, the decomposition efficiency can still be above 40%, maintaining a certain catalytic activity. This indicates that Na doping does not It not only improves the decomposition efficiency of CF4, but also prolongs the life of the catalyst, maintaining a higher catalytic efficiency over a long period of time.

[0116] Flue gas with a concentration of 10% flows through the plasma field coupled Na / mesoporous aluminum, Mn / mesoporous aluminum, Ce / mesoporous aluminum, and mesoporous aluminum respectively.

[0117] like Figure 6 As shown, Figure 6 (a) is the comparison of metal-doped mesoporous aluminum when the flue gas flow rate is 20 mL / min; Figure 6 (b) is the comparison of metal-doped mesoporous aluminum at a flue gas flow rate of 50 mL / min.

[0118] It can be seen that when the flue gas flow rate is 20mL / min, the decomposition efficiency of Mn / mesoporous aluminum on CF4 reaches a peak of 75% after 100min of reaction, and the decomposition efficiency stabilizes at about 60% after 400min of reaction. The decomposition efficiency of Ce / mesoporous aluminum on CF4 reaches a peak of 70% after 110min of reaction, and the decomposition efficiency stabilizes at about 60% after 400min of reaction. Although Mn / mesoporous aluminum and Ce / mesoporous aluminum are both lower than the maximum decomposition efficiency of 82% of mesoporous aluminum, they can still maintain a high catalytic efficiency as the reaction time increases. After 400min of reaction, the decomposition efficiency is 10% higher than that of mesoporous aluminum. After the flow rate is increased to 50mL / min, the maximum decomposition efficiency of Mn / mesoporous aluminum and Ce / mesoporous aluminum on CF4 is reduced to 60% and 62%, respectively, which is lower than the maximum decomposition efficiency of 72% of mesoporous aluminum. After 400min of reaction, the decomposition efficiency of Mn / mesoporous aluminum and Ce / mesoporous aluminum on CF4 is 50%, which is also 10% higher than that of mesoporous aluminum.

[0119] The experimental results show that Mn and Ce cannot improve the oxidation activity of mesoporous aluminum to CF4, but can prolong the catalytic reaction time. This may be because both Mn and Ce can increase the surface oxygen content, thereby strengthening the oxidation of surface carbon and reducing the carbon Deposition poisoning of catalysts.

[0120] Analysis example 4

[0121] The effect of oxygen on the decomposition efficiency of carbon tetrafluoride was studied.

[0122] Under the conditions of CF4 concentration of 10%, O2 concentration of 10%, and flow rate of 50mL / min, flue gas containing carbon tetrafluoride flows through the plasma field to couple Na / mesoporous aluminum. Figure 7 As shown, it can be seen that under anaerobic conditions, the decomposition efficiency of CF4 by plasma alone is 30%, and the decomposition efficiency drops to 26% after O2 is introduced. Under anaerobic conditions, the highest decomposition efficiency of CF4 by Na / mesoporous aluminum coupled plasma is 76%, and the decomposition efficiency drops to 46% after 400 minutes of reaction. After O2 is introduced, the highest decomposition efficiency of CF4 by Na / mesoporous aluminum coupled plasma increases to 81%, and the decomposition efficiency can still be stabilized at 60% after 400 minutes of reaction. That is, O2 increases the catalyst Decomposition efficiency and reaction stability of CF4.

[0123] Under the conditions of CF4 concentration of 10%, O2 concentration of 10%, and flow rate of 50mL / min, flue gas containing carbon tetrafluoride flows through plasma field coupled Na / mesoporous aluminum, plasma field coupled mesoporous aluminum, plasma field coupled Mn / mesoporous aluminum, plasma field coupled Ce / mesoporous aluminum, and single plasma field, respectively, to study the effect of O2 on the decomposition performance of CF4 of different metal-doped mesoporous aluminum, such as Figure 8 As shown, Figure 8 (a) Comparison of CF4 degradation efficiency of metal-doped mesoporous aluminum under oxygen-containing flue gas conditions; Figure 8 (b) Comparison of CF4 degradation efficiency of composite metal-doped mesoporous aluminum under oxygen-containing flue gas conditions.

[0124] It can be seen that the decomposition efficiency of CF4 by mesoporous aluminum coupled plasma is 58%, and after 400 minutes of reaction, the decomposition efficiency of CF4 is the same as that under the action of plasma alone, indicating that the mesoporous aluminum has been deactivated at this time. The highest decomposition efficiency of CF4 by Mn / mesoporous aluminum and Ce / mesoporous aluminum is 58%, and they are also deactivated after 400 minutes of reaction. The effects of Na, Ce, Mn, and multi-metal doping on the decomposition performance of mesoporous aluminum CF4 were studied, such as Figure 8 (b) Co-doping with Ce and Mn did not improve the CF4 decomposition activity of the catalyst, but The catalytic activity of mesoporous aluminum doped with Na alone is even weaker.

[0125] Analysis example 5

[0126] The morphology of Na / mesoporous aluminum before and after the reaction at an O2 concentration of 10% in Example 4 was studied by SEM. Fig. 9 As shown, Fig. 9 (a) is the morphology of Na / mesoporous aluminum before reaction. Fig. 9(b) is the morphology after Na / mesoporous aluminum reaction. Visible reaction The nanoparticles on the surface of Na / mesoporous aluminum are closely arranged before the reaction, and there is no obvious change on the surface of Na / mesoporous aluminum after the reaction, indicating that the reaction has not Changing the morphology of Na / mesoporous aluminum .

[0127] XPS was used to analyze the changes in element content before and after the Na / mesoporous aluminum reaction. Fig.10 As shown. Before the reaction, Na / mesoporous aluminum showed characteristic peaks belonging to Al 2p, C 1s, O 2p and Na 1s at 75.08eV, 285.12eV, 532.56eV and 1072.15eV, respectively. After the reaction, the intensity of the characteristic peak of O1s was significantly weakened, and a characteristic peak belonging to F1s appeared at 687.08eV. The changes in the element content before and after the reaction of Na / mesoporous aluminum were further analyzed, as shown in Table 1. After CF4 decomposition, the Al and O element contents on the surface of Na / mesoporous aluminum decreased by 15.15% and 26.62%, respectively, indicating that the two participated in the CF4 decomposition reaction. The C element content increased from 10.25% to 13.26%, an increase of 3.01%, which was much lower than the 30% increase in carbon element after the mesoporous aluminum reaction, indicating that Na doping promoted the combination of C and O in CF4 to generate gas escape, significantly reducing C deposition. After the reaction, the proportion of F element on the surface of Na / mesoporous aluminum is 39.87%, which is much higher than the 10.07% increase in F on the mesoporous aluminum after the reaction. Although more F is deposited on the surface of Na / mesoporous aluminum, Na / mesoporous aluminum has a higher catalytic efficiency. This indicates that Na can slow down the poisoning of mesoporous AlF.

[0128] The element contents before and after the Na / mesoporous aluminum reaction are shown in Table 1.

[0129] Table 1 Element contents before and after Na / mesoporous aluminum reaction

[0130]

[0131] The morphology of mesoporous aluminum before and after the reaction at an O2 concentration of 10% in Example 4 was studied by SEM. Fig.11 As shown in the figure, after the reaction, the pores on the surface of the mesoporous aluminum are corroded, and a large amount of C and F are deposited on the surface of the mesoporous aluminum to form a dense layer. Again It is clear that Na doping can alleviate the catalyst poisoning problem caused by C and F deposition during the catalytic reaction process .

[0132] Analysis example 6

[0133] The morphology of Na / mesoporous aluminum before and after the reaction at an O2 concentration of 10% in Analysis Example 4 was studied by XRD and TEM.

[0134] like Fig.12 As shown, Fig.12 (a) is the XRD diffraction pattern of Na / mesoporous aluminum after reaction; Fig.12(b) is the TEM image of Na / mesoporous aluminum after reaction. It can be seen that there is no obvious characteristic peak in the XRD diffraction pattern of Na / mesoporous aluminum before the reaction, indicating that the material is amorphous. After the reaction, Na / mesoporous aluminum has obvious characteristic peaks at 17°, 21° and 23°, which match AlF3-PDF47-1659, indicating that AlF3 is generated after the reaction. Fig.12 (b) shows that the lattice spacing of Na / mesoporous aluminum is 0.41 nm, which is consistent with the AlF3 (201) crystal plane spacing corresponding to 21.4° in the XRD diffraction pattern, further proving that the new substance generated is AlF3.

[0135] Analysis example 7

[0136] The changes of the surface acid sites of Na / mesoporous aluminum before and after the reaction under the condition of 10% O2 concentration in Analysis Example 4 were studied by NH3-TPD. Fig.13 As shown, Fig.13 (a) is the NH3-TPD diagram of Na / mesoporous aluminum, Ce / mesoporous aluminum and mesoporous aluminum before reaction. Fig.13 (b) NH3-TPD diagram before Na / mesoporous aluminum reaction.

[0137] Mesoporous aluminum has obvious characteristic peaks at 350℃-500℃, corresponding to strong acid sites with a content of 1.79mmol / g. Compared with mesoporous aluminum, the strong acid content of Na / mesoporous aluminum increases to 1.91mmol / g, and weak acid sites appear at 100-150℃ with a content of 0.28mmol / g. This indicates that Na doping increases the acid content on the surface of mesoporous aluminum and promotes the decomposition of CF4. Compared with mesoporous aluminum, the strong acid content of Ce / mesoporous aluminum decreases by 0.96mmol / g, and weak acid sites appear with a content of 0.26mmol / g. This indicates that Ce doping reduces the strong acid content of mesoporous aluminum, thereby reducing its decomposition efficiency of CF4. After the reaction, the weak acid content on the surface of Na / mesoporous aluminum increased to 0.35mmol / g, while the amount of strong acid decreased to 1.28mmol / g. This indicates that the strong acid sites are involved in the decomposition of CF4 .

[0138] The changes in the acidic species of Na / mesoporous aluminum before and after the reaction under the condition of 10% O2 concentration in Analysis Example 4 were studied by NH3-TPD. Fig.14 As shown, Fig.14 (a) is the infrared spectrum of pyridine adsorption before Na / mesoporous aluminum reaction. Fig.14 (b) is the infrared spectrum of pyridine adsorption after Na / mesoporous aluminum reaction.

[0139] Table 2 shows the Na / mesoporous aluminum L acid and B acid contents in this analysis example.

[0140] Table 2 Na / mesoporous aluminum L acid and B acid content before and after reaction

[0141]

[0142]

[0143] The basic sites of Na / mesoporous aluminum before and after the reaction were analyzed by CO2-TPD, such as Fig.15 As shown, Fig.15 (a) is the CO2-TPD diagram of mesoporous aluminum and Na / mesoporous aluminum. Fig.15 (b) CO2-TPD diagram of Na / mesoporous aluminum before and after the reaction.

[0144] It can be seen that mesoporous aluminum has CO2 desorption peaks corresponding to weak alkaline sites and strong alkaline sites at 100℃ and 400℃, with contents of 0.85mmol / g and 0.5mmol / g, respectively. Compared with mesoporous aluminum, the weak base content of Na / mesoporous aluminum increases to 1.15mmol / g, and the strong base content increases to 1.2mmol / g. The presence of Na is beneficial to the activation of adsorbed water and can promote the formation of surface hydroxyl groups, thereby increasing The -OH content on the surface of mesoporous aluminum was increased. After the reaction, the weak alkaline sites of Na / mesoporous aluminum disappeared, and the content of strong alkaline sites increased to 2.15mmol / g. This shows that -OH participates in the decomposition of CF4, not only giving H protons to play the role of acidic sites, but also participating in the oxidation reaction after giving protons. At the same time, the alkaline site may also come from the active oxygen ions generated by plasma-excited O2. Will adsorb on the surface and form new oxygen sites.

[0145] Analysis example 8

[0146] Mechanism Analysis of Decomposition of Carbon Tetrafluoride by Na / Mesoporous Aluminum

[0147] XPS was used to study the Na / mesoporous aluminum before and after the reaction under the condition of 10% O2 concentration in Analysis Example 4. Fig.16 As shown, Fig.16 (a) is the 2p orbital electron energy spectrum of Na / mesoporous aluminum element before and after the reaction. Fig.16 (b) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum oxide before and after the reaction. Fig.16 (c) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum sodium element before and after the reaction. Fig.16 (d) is the 1s orbital electron energy spectrum of Na / mesoporous aluminum fluoride element.

[0148] It can be seen that the main peak of the Al 2p orbital before the reaction is located at 74.24 eV, corresponding to Al-OH, and moves to 76.18 eV after the reaction, corresponding to AlF3, indicating that Al-OH participates in the decomposition reaction of CF4 and loses electrons to transform into AlF3. Fig.16 (b) is the O1s spectrum. The characteristic peaks at 530.95eV and 531.79eV before the reaction correspond to O ads and -OH, accounting for 31.4% and 68.6% respectively. Compared with mesoporous aluminum (see Table 4), the -OH content of Na / mesoporous aluminum increases by 12.6%, It is further proved that Na doping increases the surface -OH content .

[0149] After the reaction, the -OH content of Na / mesoporous aluminum decreased from 69.6% to 34.1%, and a CO characteristic peak appeared at 533.73 eV, accounting for 28.2%. This indicates that -OH participated in the decomposition reaction of CF4 and combined with C in CF4 to convert into CO. Before the reaction, Na 1s had a broad peak at 1071.39 eV, which belonged to Na-OH, and after the reaction, it moved to 1071.81 eV, corresponding to NaF. After Na doping, Al-OH The transformation into a double bridged hydroxyl group between Na and Al (HO-μbri(Na-Al)) increases the stability of -OH in Na / mesoporous aluminum, making it Not easily destroyed by O2 , maintaining a higher CF4 decomposition efficiency under O2, and O2 itself can promote carbon deposit oxidation under the action of plasma, so after Na doping, O2 changes from an inhibitory effect to a promoting effect. Fig.16 As shown in d, there are two characteristic peaks in F1s after the reaction, namely NaF

[107] (683.88 eV) and AlF3 (686.43 eV), accounting for 8.4% and 91.6%, respectively, indicating that Na-OH participates in the decomposition reaction of CF4 and is converted into NaF, which enables Na / mesoporous aluminum to maintain a higher catalytic activity during long-term reactions.

[0150] Table 3 shows the element valence ratio of Na / mesoporous aluminum before and after the reaction.

[0151] Table 3 Element valence ratio of Na / mesoporous aluminum before and after reaction

[0152]

[0153] Table 4 XPS bond valence content analysis of mesoporous aluminum

[0154]

[0155]

[0156] Analysis example 9

[0157] Analysis of Oxygen Promoted Decomposition of Carbon Tetrafluoride

[0158] In order to study the reason why O2 promotes the decomposition of CF4 by Na / mesoporous aluminum coupled plasma, Na / mesoporous aluminum was pretreated with plasma in 10% O2 and 90% Ar atmosphere, and the changes in its acid-base content were analyzed. Fig.17 As shown, Fig.17 (a) NH3-TPD diagram of O2-pretreated and untreated Na / mesoporous aluminum; Fig.17 (b) CO2-TPD of Na / mesoporous aluminum treated with O2 and without treatment. Fig.17As shown in (a), after O2 pretreatment, the weak acid site content of Na / mesoporous aluminum increased from 0.28mmol / g to 0.35mmol / g, and the strong acid site content remained unchanged. This shows that under the action of plasma, O2 does not affect the strong acid site content of Na / mesoporous aluminum. Fig.17 As shown in (b), after O2 pretreatment, the weak alkaline site content of -OH in Na / mesoporous aluminum decreased by 0.03mmol / g, while the weak alkaline site content of mesoporous aluminum decreased by 0.8mmol / g after O2 pretreatment. Na doping increases the stability of -OH, thereby significantly reducing the content of -OH destroyed by O2. Since O2 is beneficial to the oxidation of carbon on the catalyst surface, it promotes the decomposition of CF4. Therefore, O2 can transform the inhibitory effect of O2 into a promoting effect on the catalytic decomposition of CF4 on Na / mesoporous aluminum.

[0159] In order to study the effect of catalyst on CF4 decomposition products under aerobic and anaerobic conditions, the gas chromatogram of CF4 tail gas was analyzed, such as Fig.18 As shown. Under anaerobic conditions, the products of CF4 decomposition by Na / mesoporous aluminum contain CO2, CO, and CH2F2. After adding oxygen, the characteristic peaks of CO and CH2F2 disappear, and the CO2 peak increases. The product of CF4 decomposition by Ce / mesoporous aluminum has the same peak as that of Na / mesoporous aluminum, indicating that the catalyst does not affect the product of CF4 decomposition.

[0160] In summary, Na doping increases the -OH content in mesoporous aluminum and forms double-bridged hydroxyl groups (HO-μbri(Na-Al)). The Na / mesoporous aluminum surface is present in a state, which enhances the stability of -OH. The increase in O content in Na / mesoporous aluminum promotes the combination of C in CF4 with O to generate gas escape, reducing C deposition. After the reaction, Na / mesoporous aluminum combines with F in CF4 to generate NaF and AlF3 deposited on the catalyst surface.

[0161] Under the action of plasma, CF4 is excited to react and the CF bond breaks. The F atom forms HF with -OH, and HF combines with Al and Na to form AlF3 and NaF, which are deposited on the catalyst surface. Part of C is directly deposited on the catalyst surface, and part of it forms CO and CO2 with O after the break of -OH. Some of the CF4 that is not completely decomposed combines with -OH to form CH2F2. After O2 is introduced, CH2F2 and CO are oxidized and converted into CO2.

[0162] Analysis example 10

[0163] The mesoporous aluminum, commercial Al2O3, and non-catalytic material (blank control group; the figure shows single plasma) prepared in Comparative Example 2 were respectively coupled to a plasma reactor with an input voltage of 25 kV to carry out a comparative experiment on the decomposition of carbon tetrafluoride.

[0164] That is, a 10% carbon tetrafluoride gas was flowed at a flow rate of 10 mL / min through the mesoporous aluminum (shown as mesoporous aluminum), commercial Al2O3 (shown as commercial Al2O3), and a catalytic material-free (blank control group; shown as plasma alone) prepared in Example 1, all of which were in a low-temperature plasma field formed by a plasma reactor with an input voltage of 25 kV, to perform carbon tetrafluoride decomposition treatment, and the decomposition efficiency of the treatment from 0 to 600 min was recorded, as shown in detail. Fig.19 shown.

[0165] according to Fig.19 As shown in the figure, the decomposition efficiency of CF4 by mesoporous aluminum rapidly increased to 85% within the initial 200 minutes, and then slowly increased to a peak of about 99% after about 400 minutes. Under the same conditions, the peak decomposition efficiency of commercial Al2O3 for CF4 was only 74%, and the decomposition efficiency dropped to below 50% at 300 minutes, which was equivalent to the decomposition efficiency of CF4 by plasma alone, indicating that the commercial Al2O3 had been deactivated at this time.

[0166] The comparison of specific surface area, pore volume and pore size of commercial alumina and mesoporous aluminum is shown in Table 5.

[0167] Table 5 Comparison of specific surface area, pore volume and pore size of catalysts

[0168]

[0169] Analysis example 11

[0170] NH3-TPD was used to analyze the changes in the surface element composition of the mesoporous aluminum before and after the reaction in the case of CF4 concentration of 10%, oxygen concentration of 10%, and flue gas flow rate of 20ml / min in Analysis Example 4. Fig. 20 As shown. It can be seen that before the reaction, the mesoporous aluminum has a characteristic peak at 300-500℃, corresponding to the strong acid site, with a content of 1.79mmol / g. After the reaction, the content of the strong acid site on the surface of the mesoporous aluminum dropped to 1.11mmol / g, and a new characteristic peak belonging to the weak acid site appeared at 100℃, with a content of 0.35mmol / g. The results show that the strong acid site is involved in the CF4 decomposition reaction.

[0171] This example also performs NH3-TPD test on the commercial alumina in Analysis Example 10, as shown in FIG. Fig. 20 As shown in the figure, compared with mesoporous aluminum, the desorption peak of NH3 on commercial alumina during the NH3-TPD test appears at a higher temperature, and the content of strong acid sites is 1.54mmol / g, which is much lower than that of mesoporous aluminum. The mesoporous aluminum surface contains a higher content of strong acid, thus showing higher CF4 catalytic activity.

[0172] The specific conclusions are as follows:

[0173] (1) The Na / mesoporous aluminum prepared by doping with 5% Na has the best catalytic performance, which not only improves the decomposition efficiency of CF4, but also prolongs the life of the catalyst, allowing it to maintain a higher catalytic efficiency for a long time. Mn and Ce doping cannot improve the oxidation activity of mesoporous aluminum for CF4, but can prolong the effective time of the catalytic reaction. After the introduction of O2, the decomposition efficiency and reaction stability of Na / mesoporous aluminum for CF4 were improved, while the decomposition activity of Mn / mesoporous aluminum and Ce / mesoporous aluminum for CF4 was not improved.

[0174] (2) Na doping is beneficial to the activation of adsorbed water, which can promote the formation of surface hydroxyl groups and increase the content of mesoporous aluminum acidic and basic sites, thereby promoting the decomposition of CF4.

[0175] The Al-OH in mesoporous aluminum is transformed into a double-bridged hydroxyl group between Na and Al (HO-μbri(Na-Al)), which enhances the stability of -OH. After the introduction of O2, the strong acidic sites and hydroxyl content of Na / mesoporous aluminum do not change significantly, enabling it to maintain a higher CF4 decomposition efficiency under O2.

[0176] (3) Na doping promotes the combination of O and C in CF4, generating gas escape, which significantly reduces C deposition. After the reaction, Na / mesoporous aluminum combines with F in CF4 to generate NaF and AlF3 deposited on the catalyst surface, significantly increasing the surface F deposition. However, Na / mesoporous aluminum has a higher catalytic efficiency, indicating that Na can slow down the F poisoning of mesoporous aluminum.

[0177] In summary, the above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A sodium-modified mesoporous aluminum, characterized in that: It comprises a mesoporous aluminum substrate and metallic sodium, wherein the metallic sodium is uniformly dispersed in the mesoporous aluminum substrate, and the mesoporous aluminum substrate is porous nanoparticles in an amorphous state; The mass proportion of oxygen elements on the surface of the sodium-modified mesoporous aluminum is 40% to 50%, the mass proportion of sodium elements on the surface of the sodium-modified mesoporous aluminum is 1 to 20%, and the specific surface area of ​​the mesoporous aluminum substrate is ≥100m 2 / g, and the pore size of the mesoporous aluminum substrate is 2-50nm.

2. The sodium-modified mesoporous aluminum according to claim 1, characterized in that The mass proportion of the sodium element on the surface of the sodium-modified mesoporous aluminum is 3-5%.

3. A method for preparing sodium-modified mesoporous aluminum according to any one of claims 1 to 2, characterized in that: Includes steps: Mixing polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture; The mixture is sequentially subjected to stirring treatment, drying treatment and calcination treatment to obtain sodium-modified mesoporous aluminum; The metal nitrate includes sodium nitrate, and the added amount ratio of the polyether, the nitric acid, the aluminum isopropoxide and the sodium nitrate is 1g:1.5ml:10mmol:0.01-0.05g, wherein the concentration of the nitric acid is 65%.

4. The preparation method according to claim 3, wherein the temperature of the calcination treatment is 500-1000°C, and the duration of the calcination treatment is 1-8 hours.

5. The preparation method according to claim 4, characterized in that: In the step of mixing the polyether, nitric acid, aluminum isopropoxide and metal nitrate to obtain a mixture, the polyether is dissolved in a solvent, and the nitric acid, aluminum isopropoxide and metal nitrate are added under stirring; wherein the mass volume ratio of the polyether to the solvent is 0.01 to 1 g / ml.

6. The preparation method according to claim 4, characterized in that: The temperature of the drying process is 50 to 80° C., and the duration of the drying process is 6 to 12 hours.

7. The preparation method according to claim 6, characterized in that: The temperature of the calcination treatment includes 600° C., and the calcination treatment includes: heating the solid particles obtained by the drying treatment to 600° C. at a heating rate of 1-10° C. / min, and calcining for 3-6 hours to obtain the sodium-modified mesoporous aluminum.

8. Use of sodium-modified mesoporous aluminum prepared by the preparation method according to any one of claims 4 to 7 in carbon tetrafluoride treatment, characterized in that: Includes steps: The carbon tetrafluoride-containing flue gas to be treated flows through the sodium-modified mesoporous aluminum in a plasma field for decomposition treatment, the flow rate of the carbon tetrafluoride-containing flue gas in the plasma field is 10-50 mL / min, and the concentration of carbon tetrafluoride in the carbon tetrafluoride-containing flue gas is 1%-20%; The sodium-modified mesoporous aluminum is placed in the discharge region of the plasma field.

9. The use according to claim 8, characterized in that: The input voltage of the plasma reactor for forming the low-temperature plasma field is 20-40 kV.

10. The use according to claim 8, characterized in that: The oxygen concentration in the carbon tetrafluoride-containing flue gas is 5%-20%.

Citation Information

Patent Citations

  • Preparation method of mesoporous alumina composite adsorbent functionalized by alkali metal

    CN102698704A

  • Ordered alumina mesoporous material and preparation method thereof

    CN107010648A

  • Mesoporous alumina-based core-shell composite material as well as single micelle guide interface assembly method and application thereof

    CN113548684A

  • Core-shell-shaped alumina microsphere catalyst, preparation method thereof and application of core-shell-shaped alumina microsphere catalyst in catalytic decomposition of CF4

    CN118162122A

  • Preparation of modified mesoporous alumina and application of modified mesoporous alumina in preparation of propylene through propane dehydrogenation

    CN118204075A